Gabapentinoid use, risks, and the impact of reclassification for chronic pain patients in the United Kingdom - ALFRIAH, JOUD (2024)
Background: Chronic pain is a significant health concern in the UK, leading to increased use of pregabalin and gabapentin beyond their original indications for epilepsy, anxiety, and neuropathic pain. This expanded, often unlicensed use has raised concerns due to limited efficacy evidence and misuse risks, especially with opioids. Consequently, gabapentinoids were reclassified as Schedule III controlled drugs in the UK in 2019. This study utilised CPRD data to examine gabapentinoid prescribing patterns from January 2005 to December 2020 and assessed the impact of reclassification on prescribing trends, focusing on chronic pain patients. Moreover, it explored the association between gabapentinoid use and harms from August 2012 to July 2020.